Transcriptional and genomic analyses reveal an analogous mechanism for a Piperidinyl-Benzimidazolone analog in Babesia divergens compared to other apicomplexans - Maritz-Olivier, Christine (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2015.